Analisis Struktur Penceritaan Webtoon Horor Creep Episode 11 - Basyarayni Mawla Fatha; Alvanov Zpalanzani Mansoor (Universitas Multimedia Nusantara, 2021)
Webtoon is a form of graphic narrative that interweaves words and images through panel arrangement like a printed comic. However, webtoon’s vertical orientation is one of the few differing factors that excludes webtoon from the printed comic category. Like other genres in fictional graphic narrative, horror webtoon also adjusts its narrative structure through some of webtoon’s building aspects. This research aims to find out how the horror atmosphere is built in a popular Indonesian horror webtoon titled Creep created by Ino Septian by examining one of the representative episodes. This analysis is conducted by applying Zpalanzani's triangulation analysis model perfected by adding the structural affect theory of stories by Brewer and Lichtenstein. The results of this study indicate that some building aspects of webtoon such as the gutter space, the vertical orientation of the canvas, and the arrangement of the text that connects each panel are utilized to build the horror narrative and atmosphere. These three aspects provide the readers with a more emotional experience of the horror itself. Keywords: horror; webtoon; visual narrative